Asuhan Keperawatan Jiwa pada Pasien Skizofrenia Paranoid dengan Halusinasi Penglihatan di RSJD dr. Arif Zainudin Jawa Tengah - Reni Niken Astutik; Cipto (Journal of Medical Practice and Research, 2025)
Mental health is a vital aspect of overall well-being, involving physical, psychological, social, and spiritual balance. Schizophrenia, a chronic psychiatric disorder, significantly affects quality of life and social functioning, particularly when accompanied by visual hallucinations. This study aimed to describe psychiatric nursing care for patients with paranoid schizophrenia experiencing visual hallucinations at RSJD Dr. Arif Zainudin, Central Java. A qualitative case study was conducted with two inpatients in the Gatotkaca ward. Data were collected through semi-structured interviews, behavioral observations, physical examinations, and medical record reviews, followed by descriptive-comparative analysis. The findings showed that nursing care was delivered systematically, covering assessment, diagnosis, planning, implementation, evaluation, and documentation. Interventions included health education, hallucination confrontation techniques, adherence to medication, structured daily activities, and family involvement. These approaches effectively reduced hallucination intensity and enhanced coping abilities. Continuous evaluations demonstrated improvements, with patients becoming more aware of their symptoms, applying distraction strategies, and showing better social interactions. This study emphasizes that evidence-based interventions and strong family support are crucial in the recovery process of patients with paranoid schizophrenia.